A conceptual model of nurse retention integrating quality of work life and human resource management: the case of Jordan - Abdel Rahman Gharaibeh, Muna Bassam; Mansor, Zuraina; Raja Yusof, Raja Nerina (Macrothink Institute, 2024)
Worldwide, the health sector faces a major challenge in retaining its staff. In Jordan, both public and university hospitals struggle with high turnover among nursing staff, which ultimately affects their overall performance. This study aims to discuss an integrated conceptual model that is developed based on the impact of quality of nursing work life (QNWL) and human resource management (HRM) practices on nursing staff retention. The model is drawn using the socio-technical system (STS) and social exchange (SET) theories to support the significance of QNWL and nurse retention. In addition, HRM practices involving training, compensation, performance appraisal, and recruitment were used. This framework contributes to research by combining the perspectives of QNWL and HRM to understand employee retention comprehensively. The practical insights derived from this model can be used to improve nurse retention strategies in the Jordanian healthcare system and as a foundation for future empirical research.